(untitled) (LACCEI, 2024)
With the increasing number of connected IoT devices for 5G networks, numerous access schemes have been conceived in the literature. Although several cross-layer (PHY MAC) approaches have been reported in the literature, some aspects regarding their implementation on testbeds are overlooked. In this work, we address the prototyping of low power wide area (LPWA) networks aiming to fill the existing mismatching performance between theoretical and experimental results. In doing so, the main aspects and current challenges are explored with the prototyping of access schemes using reinforcement learning (RL) techniques. The missing implementation aspects omitted during the modelling of these networks are reviewed and addressed by employing software-defined radio (SDR) approaches. Finally, at the light of the exposed implementations, some guidelines and suggestions for the development of this technology are provided.